Oral bioavailability and egg drug residue of lincomycin in laying hens after different treatment - Jin-Hwa Kim; Je-Won Ko; Jeong-Won Kim; Ji-Soo Jeong; Chang-Yeop Kim; In-Sik Shin; Tae-Won Kim (Poultry Science, 2024)
ABSTRACT: Lincomycin (LCM) is an antibiotic used to treat severe bacterial infections in livestock and companion animals. In this study, we aimed to investigate the oral bioavailability of LCM with PK data after IV and PO administration and to compare differences in drug residue patterns in eggs. To ensure food safety, an additional study on egg residue was conducted using 3 different commercial LCM drugs. For bioavailability study, laying hens were divided into oral and intravenous (n = 8/group) groups and received single dose (10 mg/kg) of LCM. The limits of quantification for LCM were 0.729 μg/mL and 0.009 mg/kg in plasma and eggs, respectively. The oral group exhibited a significantly lower average serum drug concentration than the IV group, with a bioavailability of 2.6%. Furthermore, the egg residue profiles confirmed reduced systemic drug exposure after oral administration. For the commercial LCM drug egg residue experiment, laying hens were divided into low- and high-dose groups (n = 12/group) for each drug and treated with the recommended dosage and administration method for each respective drug. The eggs were collected and analyzed until 14 d after the last drug treatment. Despite differences in the LCM content and formulation among commercial drugs, all the tested commercial drugs showed average concentrations below the MRL in eggs within approximately 3 d after the last drug treatment. In this study, we have confirmed that LCM has a low oral absorption rate in laying hens, and this was consistent with the findings from the egg residue profiles. Further studies are requested to elucidate the exact reasons for evidently low oral drug absorption in laying hens.